A new nutritional screenig tool; gnri in japanese incident dialysis patients. - Sawako Kato; Yoshinari Yasuda; Yukio Yuzawa; Yoshinari Tsuruta; Shoichi Maruyama (The Korean Society of Nephrology, 2012)
Background: Inflammation and malnutrition are common in chronic kidney disease (CKD) patients and among strong predictor of cardiovascular disease (CVD). Geriatric nutritional risk index [GNRI=1.489×albumin (g/dl) +41.7(body weight (BW) / ideal BW)] has been reported to be a simple and accurate nutritional screening tool in CKD patients as well as old people. Previous studies demonstrated low lymphocyte count (LLC) predicts poor outcome in patients with CVD and heart failure. Methods: A total of 68 Japanese incident dialysis patients (44 males, mean age 61±11 years) were enrolled and followed in an ongoing prospective study. Nutritional status [albumin, body mass index (BMI), abdominal circumstances, subjective global assessment (SGA) and GNRI] was assessed. Inflammatory biomarkers including white blood cell count (WBC) and differential were determined. Results: The median of GNRI was 95.4. When divided into two groups by the median, there were no association in age, gender, diabetes, SGA, medications including ESA between two groups. GNRI showed significantly correlation to hemoglobin (ρ=0.31, p=0.014) and did negatively correlation to WBC count (ρ=−0.24, p=0.049) and ferritin (ρ=−0.27, p=0.021) in Spearman's rank test. Although these associations disappeared 1 year after initiation of dialysis therapy, the patients with higher incremental GNRI significantly showed increased lymphocyte count. Conclusion; Our results suggest that GNRI is a simple nutritional tool for dialysis patients and that GNRI might detect inflammation and predict CVD.